(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The paper examines recent ideas about the use of new technology in History education, contrasting the ideas of policy makers, initial teacher education curriculum specifications, and expert practitioners in the field of school history and new technology. The paper draws on Stephen J Ball’s theoretical framework which considers changes in education policy in the light of the context of influence (who were the policy makers in charge at the time), the context of text production (what were the key policy documents influencing change), and the context of practice (what were the views of practitioners). A more developed explanation of this framework can be found in Phillips, 1998:5-7). It argues that there has been a disconnection between the views of expert practitioners and those making policy, and considers the implications of radical recent changes in the way that young people get their information about the past – and the present. This raises the question of what it means ‘to be good at ICT’ as a History teacher; what should our priorities be in terms of the training of History teachers? The concluding section of the paper argues that less attention should be given to issues of general technological competence, and greater emphasis should be placed on the development of skills of information literacy, in a society that has recently been widely described as a ‘post-truth’ society. Although the focus of the paper is largely on developments in England, the issues explored have relevance to History education in other countries.